Development of Slot-Less Linear Oscillatory Actuator - Raja Othman, Raja Nor Firdaus Kashfi (2009)
Linear Oscillatory Actuator (LOA) is an electromechanical device that can produce short linear stroke motion directly without the use of any mechanical transmission to convert rotary motion into linear motion. Due to this simplicity, the benefits of LOA over conventional actuator are simple structure, better dynamical performance, and higher reliability. It has been extensively used in industry applications especially in power generation, healthcare, factory automation, and household appliances. Currently, most of the researches are only dealing with designing a slot type of LOA with exact values of thrust, electrical time constant, and mechanical time constant. Some of them studied the control strategy of an existing moving coil type of LOA. But, none of them had disclosed information about the oscillation displacement characteristics based on various sizes of LOA. Such information is useful for the designer. It will provide solutions or guidelines about the thrust constant, spring constant, electrical time constant, and mechanical time constant toward oscillation displacement characteristics of LOA. The analysis of the parameters mentioned above definitely will help any researchers to know whether the LOA is suitable for the specific application before design the optimized structure for fabrication. Unfortunately, the information as mentioned above is not available to the designers. This thesis describes the development and analysis on the effect of thrust constant, spring constant, electrical time constant, and mechanical time constant to oscillation displacement characteristic of slot-less linear oscillatory actuator. The analysis is necessary to determine the variation and relationship of these constants to various sizes of LOA. In this research, a prototype of slot-less linear oscillatory actuator is designed using Finite Element Method (FEM). The prototype is fabricated and measured experimentally. Moreover, analytical solution is developed for the same prototype using Permeance Analysis Method (PAM). The two methods were verified through comparison with measurement. The comparison shows the proposed analytical solution using PAM had good agreement with both FEM and the measurement. As summary, the research found that the constants affect the oscillation displacement to be higher but the thrust would become lower for small size of LOA. In contrary, high thrust can be achieved for bigger size of LOA but the oscillation displacement would become lower. Therefore, in order to design high thrust LOA the lower value of electrical time constant and mechanical time constants should be selected. Meanwhile, for both thrust constant and spring constant higher value should be selected. For designing higher oscillation displacement of LOA, the lower value of electrical time constant, thrust constant, and spring constant should be selected where as for mechanical time constant higher value should be selected.